Analyzing Scientific Perspectives on the Basis of Financial Strategy in the Formation of Financial Policy - Nigora, Primova (Researchparks Publishing, 2023)
In this study, the laws, trends and opportunities of financial strategy formation have been studied on the scientific basis of the financial policy formation under conditions of Uzbekistan, the scientific perspectives of scholars and experts have been analyzed to study the formation of regional financial policy and its specific features.